Breast Cancer Screening (BCS) by Mammography Tomosynthesis. (13th November 2019) - Correia, M; Aleixo, F; Lagoa, A; Ferrinho, D; Pereira, R; Vale, L; Cardoso, C; Faria, M
Abstract: Issue: Breast cancer is the 2nd cause of death for women in Portugal and 6000 new cases are detected annually. The prognosis is better for women whose cancers are detected earlier. Description: Algarve BCS begin in 2005 using a digital mammography with 2 incidences/breast with double reading and consensus by a 3rd radiologist. Each 2 years women age 50 to 69, are invited to a Mobile Unit to do the mammography, a partnership with Algarve Oncologic Association. In 2017, direct digital mammography with Tomosynthesis(DDMT)was implemented. This technique increase cancer detection, reduction of false positives, false negatives and radiation dose. Diagnostic accuracy is better and also improves accessibility to the most vulnerable population groups to this technology. Results: BCS covers 100% of the region and the mobile unit is user friendly for women with mobility impairment. Adhesion rate is > 62%. Is the 1st screening using Tomosynthesis in Portugal.Preliminary results show that the confirmation rate increased (10 %), the detection rate per 1.000 women also increased and the positive predictive value >95%. Costs associated with the program decrease and less number of women called for false positives is observed. The number of positive mammograms increased, due to diagnostic acuity, with better visualization of the breast, namely in the patterns of greater mammary density; which leads to an improvement in further assessment rates. Lessons: The technique increases the adhesion rate, with the same human resources. The decrease of the false positives improves the number of women send to further assessment and Senology Center. Earlier diagnoses, less aggressive treatments, and a higher survival rate are also expected. Messages- Using this technology is expected that cancer diagnosis will be earlier, more reliable and wiht higher survival rate for this disease. The possibility of a population based screening with DDMT is an opportunity to reduce inequalities in the region. Key messages: Mammography Tomosynthesis is expected that cancer diagnosis will be earlier, more reliable and wiht higher survival rate for this disease. The possibility of a population based screening with Mammography Tomosynthesis is an opportunity to reduce inequalities in the region.